Martian Mantle Heat Flow Estimate From the Lack of Lithospheric Flexure in the South Pole of Mars: Implications for Planetary Evolution and Basal Melting. Issue 2 (18th January 2021) - Ojha, Lujendra; Karimi, Saman; Buffo, Jacob; Nerozzi, Stefano; Holt, John W.; Smrekar, Sue; Chevrier, Vincent
Abstract: Heat flow measurements are important for our understanding of planetary interior composition, structure, and evolution. In the absence of direct measurement, a first‐order estimate of a planet's interior heat flow can be made by modeling the lithosphere's viscoelastic response to stress exerted by large surface loads. Here, we model the Martian lithosphere's viscoelastic response to the south polar layered deposits and estimate the local mantle heat flow to be less than ∼10 mW/m 2 . Combined with our previous estimate of the low mantle heat flow from the north polar region (∼7 mW/m 2 ), our results suggest that the Martian mantle may be globally depleted in heat‐producing elements. The relatively low mantle heat flow has significant implications for Mars' long‐term thermal evolution and on the possibility of basal melting in the south polar region. Plain Language Summary: The outermost layer of a planet is called the lithosphere. The lithosphere can bend due to the weight of large mountains or thick glaciers. The total amount of the bending depends on the stress imparted by topographic loads and strength or thickness of the lithosphere, which depends on the planet's interior heat. Despite the huge amount of stress exerted by the south polar cap of mars, the lithosphere underneath is remarkably flat. In this work, we model the lithospheric bending using numerical methods and provide a first‐order estimate of the heat being generated in the Martian mantle. Our results suggest that the lithosphere in the southern polar region is thick and that Mars' interior is relatively cool. Key Points: We estimate the mantle heat flow in Mars's south polar region to not exceed 10 mW/m 2 The low mantle heat flow estimate suggests the Martian mantle to be depleted in heat‐producing elements Based on our heat flow constraints, present‐day basal melting of the south polar layered deposits is highly unlikely